POPULATION DYNAMICS AND MONITORING OF SUCKING PESTS AND BOLLWORMS ON BT COTTON IN HUMID ZONE OF SOUTHERN RAJASTHAN - BABU, S. RAMESH; MEGHWAL, MADAN LAL (The Bioscan, 2014)
The population dynamics of sucking pests and boll worms of Bt cotton along with their correlation with weather factors were studied during 2011 at the experimental farm, Agricultural Research Station, Banswara. The incidence of Jassids was observed throughout the crop season. Whitefly population was ranged from 3.9 to 42.0/3 leaves. Similarly, thrips population was in higher side and population was ranged from 0.0 to 87.0 /3 leaves. Mealy bug grade was ranged from 1.0 to 4. Moth population of Spodoptera litura noticed throughout the season while no moth catches of American bollworm with nil larvae population on Bt cotton was recorded. The peaks of moth populations of pink bollworm were recorded during 41-52nd standard week corresponding with larval population in field. Correlation studies revealed that the maximum temperature, morning relative humidity and rainy days were significant and positively correlated with the leafhopper population. Rainy days and relative humidity was the main significant contributing factor for the maximum occurrence of whitefly in Bt cotton. The main contributing weather factor for the incidence of thrips in Bt cotton was maximum temperature (r=-0.613**) and sunshine hours (r=-0.344**). The present studies revealed that the mealy bug population was increased with the increase in maximum temperature and sunshine hours. Regression models and the coefficients of determination (R2) indicated that the sucking pests viz., jassids, thrips, whitefly were predicated to an extent of 74, 62 and 43 per cent, respectively. While, the prediction rate of populations of male moth catches of spotted bollworm, pink bollworm and tobacco caterpillar were 44%, 84% and 37%, respectively during 2011. Analysis clearly showed the importance of weather factors in predicting the pest incidence in Bt cotton.